Exercise prescription: perceptions and physical activity habits in chiropractic students at CMCC - Howitt, Scott (J Can Chiropr Assoc, 2016)
BACKGROUND: Health care practitioner’s physical activity (PA) habits are associated with their likelihood to recommend PA to their patients. The intent of this project is to better understand the Canadian Memorial Chiropractic College (CMCC) students’ perceptions and practices of PA and exercise prescription as this may predict exercise counselling they will provide to future patients. METHODS: A 27-item survey was distributed to Canadian Memorial Chiropractic College (CMCC) students (N = 744). The survey determined the proportion of CMCC students that meet the (2012) Canadian Physical Activity Guidelines. Additionally the survey recorded students’ perceptions of PA counselling during patient visits and their own example of maintaining a healthy lifestyle. RESULTS: The response rate for the survey was 46% (N = 343). By using average estimates, it was determined that 72% of the respondents meet the (2012) Canadian Physical Activity Guidelines. 86% of the respondents perceived PA counselling to be usually or always relevant during patient interactions, and approximately 73% believed that exercise counselling is highly relevant to chiropractic practice. Furthermore, at least 88% percent believed that chiropractors must adhere to a healthy lifestyle in order to effectively model a healthy lifestyle to their patients. CONCLUSIONS: A high proportion of CMCC students meet PA guidelines, and perceive PA counselling to be highly relevant and important to patient encounters.